Introdução à estatística e probabilidade : uma abordagem contextualizada no cotidiano dos alunos - Duarte, Rafael Luz (2013)
The statistics from very ancient times has its importance and now even more in fields such as research and research prices of intent to vote in an election. The methods of teaching mathematics have also been developed to adapt to changing students' behavior, but are not enough new approaches to teach any content requires a theoretical well beyond what the students have prior knowledge, since the teacher should at least try to get the student to think beyond what is proposed under the initial plan. Therefore, we begin covering the theory of probability to serve as the basis for readers who may be interested in the practice of this new approach methodology of descriptive statistics, based on students' everyday lives, their experiences both at school and in the environment that they live and socialize. This methodology was applied to an entire class of 3rd year of high school E.E.M. Eliezér de Freitas Guimarães and two others remained traditional, showing satisfactory results in yield, thus learning.